2012
DOI: 10.17796/jcpd.37.1.h62037241u458571
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oxidative Potential Water as an Irrigant in Pulpectomized Primary Teeth

Abstract: Objective: The aim of this study was to evaluate the effectiveness of oxidative potential water (OPW) as an irrigating solution in reducing bacterial loading in necrotic pulpectomized primary teeth. Study design: Forty necrotic teeth were included, 20 irrigated with OPW (experimental group) and 20 with 1% NaOCl (control group); in both groups, 2 microbiological samples from within the canals were taken with a sterile paper point, the first before irrigation (immediately before opening the crown), and the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
0
16
1
1
Order By: Relevance
“…4,6,7 Studies that have examined the bacterial community of infected root canals of primary teeth before and after chemomechanical preparation (CP) are scarce in the literature. [8][9][10] These studies show a reduction in microorganisms, however, unlike the present study, they did not associate the performance of pulpectomy with the presence of microorganisms before and after CP, especially after long-term monitoring. Therefore, the analysis of this long-term correlation becomes relevant.…”
Section: Introductioncontrasting
confidence: 95%
“…4,6,7 Studies that have examined the bacterial community of infected root canals of primary teeth before and after chemomechanical preparation (CP) are scarce in the literature. [8][9][10] These studies show a reduction in microorganisms, however, unlike the present study, they did not associate the performance of pulpectomy with the presence of microorganisms before and after CP, especially after long-term monitoring. Therefore, the analysis of this long-term correlation becomes relevant.…”
Section: Introductioncontrasting
confidence: 95%
“…The efficacy of NaOCl as a control irrigant was compared with OPW, and with MTA, in terms of CFU/mL. Based on the homogeneity between the studies, it was decided to combine the results, despite their being different experimental groups.…”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis was conducted with only two studies: those of Valdez‐González et al . and of Farhin et al ,.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study showed that OPW was as effective as the NaOCl when used as an irrigant in necrotic pulpectomized primary teeth and is suggested as an alternative for irrigating primary teeth. 33 …”
Section: Electrochemically Activated Solutionsmentioning
confidence: 99%